(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A novel closed-loop control bidirectional buck-boost converter, a crucial part of a photovoltaic and energy storage system (PV-ESS), is proposed in this study. To enable zero-voltage-switching turn-on for switches, traditional bidirectional buckboost converters for ESSs run in discontinuous conduction mode (DCM). Nevertheless, low power-conversion efficiency and large output voltage and current ripples are the results of DCM operation. The suggested converter features a new combination construction that combines an auxiliary capacitor with a cascaded buck-boost converter to improve performance over the conventional converter. By offering a current path, the combined structure of the suggested converter increases efficiency while reducing output current ripple. The suggested closed-loop control converter has an output voltage ripple of less than 5.14 Vp.p. and an output current ripple of less than 7.12 Ap.p., with a maximum efficiency of 98%. These outcomes were attained using an input voltage of 160 V, an output voltage of 80 320 V, an output power of 16 160 W, and a switching frequency of 45 kHz. According to the experimental findings, the suggested converter performs better than the traditional converter.